Vitamin D Supplementation and Genetic Polymorphisms Impact on Weight Loss Diet Outcomes in Caucasians: A Randomized Double-Blind Placebo-Controlled Clinical Study - Xenos, Konstantinos; Papasavva, Maria; Raptis, Athanasios; Katsarou, Martha-Spyridoula; Drakoulis, Nikolaos (Frontiers in Medicine, 2022)
Vitamin D deficiency or insufficiency is common in obese people, with some studies suggesting that low vitamin D levels might be an independent predictor of obesity. Thus, the purpose of the present randomized, double-blind, placebo-controlled trial was to investigate the effect of oral spray vitamin D3 3000 IU supplementation along with personalized weight-loss diet on obesity markers in overweight and obese Caucasians with vitamin d deficiency or insufficiency. The impact of vitamin D receptor (VDR) and adrenergic receptors (ADRs) genetic variants on vitamin D levels and weight loss diet outcomes was also investigated. A total of 125 eligible volunteers were randomly assigned into vitamin D (vitamin D3 3000 IU oral spray supplementation, n=76) or placebo (xylitol, water, mint, n=49) group following a weight loss program (600 calories less than the total energy expenditure of each volunteer) for 3 months. Fat mass, BMI, REE, and 25(OH)D serum level were monitored on the baseline and each month. DNA samples were extracted from buccal swabs and genotyped for the rs2228570 (VDR), rs1544410 (VDR), rs731236 (VDR), rs1800544 (ADRA2Α), rs1801252 (ADRB1), rs1042713 (ADRB2), and rs4994 (ADRB3) polymorphisms. Between-group comparisons revealed significant improvement in serum 25(OH)D level and greater reduction in weight, BMI, and fat percentage in the vitamin D group compared to the placebo group (p<0.05). In the vitamin D group, carriers of the rs2228570 T allele tended to have greater vitamin D level improvement compared with the homozygous C allele (p=0.067). Furthermore, heterozygous (CT) for the rs731236 tended to have lesser weight loss (p=0.068) and for the rs1042713, a lower decline in fat percentage was observed for homozygous AA carriers compared to the heterozygous (p=0.051). In the control group, differences in weight loss (p=0.055) and BMI (p=0.045) were observed between rs1544410 AA and GG homozygous. In conclusion, vitamin D oral spray supplementation seems to improve vitamin D status and decrease obesity markers during a weight-loss intervention in overweight/obese Caucasians with vitamin D deficiency or insufficiency. Also, the results of the present study indicate that VDR and ADRs genetic polymorphisms seem to influence vitamin D supplementation response and obesity markers.